A 10-year retrospective review of stonefish sting injury in Hong Kong. Issue 5 (September 2020) - Poon, KM; Ng, Chun Ho Vember; Tse, ML
Background: Stonefish sting injury is one of the common marine stings in Hong Kong. It is commonly sustained during maritime activities, and it could be regarded as occupational hazard for chefs or domestic hazard for family. Its envenomation could lead to significant local symptoms (pain or swelling) and serious complications, including infection and compartment syndrome. Objectives: This study is to review its clinical presentation and various treatment modalities. Methodology and study design: Reported cases of stonefish stings to Hong Kong Poison Information Centre from October 2008 to October 2018 were included in the study. The cases were retrieved from the Hong Kong Poison Information Centre electronic database. Information on patient demographic data, clinical parameters (e.g. the site of injury, presenting symptoms), and various treatment modalities (e.g. analgesics, hot water immersion, and use of antivenom) was collected. Results: There were 32 eligible patients included in this case series. All of them sustained the injury over either their fingers or hands. All patients reported pain over the site of injury. Other reported symptoms included numbness (41%), swelling (81%), and redness (47%). Twenty-five patients (78%) had radiograph done, and one of them was noted to have foreign body retained at the site of envenomation. All patients received hot water immersion to the affected part at 40°C–45°C for at least 30 min. Altogether eight patients (25%) received stonefish antivenom for pain relief. One patient developed compartment syndrome and received emergency operation of fasciotomy of right hand and forearm. Conclusion: Stonefish envenomation can cause extreme pain, swelling, and erythema, which can be managed with hot water immersion, analgesics, and prophylactic antibiotics. Use of antivenom can be considered in selected case.